Evidence Use in Health Policy Making An International Public Policy Perspective - Parkhurst, Justin; Ettelt, Stefanie; Hawkins, Benjamin (Springer Nature, 2018)
This open access book provides a set of conceptual, empirical, and comparative chapters that apply a public policy perspective to investigate the political and institutional factors driving the use of evidence to inform health policy in low, middle, and high income settings. The work presents key findings from the Getting Research Into Policy (GRIP-Health) project: a five year, six country, programme of work supported by the European Research Council. The chapters further our understanding of evidence utilisation in health policymaking through the application of theories and methods from the policy sciences. They present new insights into the roles and importance of factors such as issue contestation, institutional arrangements, logics of appropriateness, and donor influence to explore individual cases and comparative experiences in the use of evidence to inform health policy.